Pendekatan Konseling Behavioral Dengan Teknik Reward and Punishment Dalam Meningkatkan Motivasi Kerja - Umam, Muhamad Safiul (Universitas Pendidikan Ganesha, 2024)
Companies are required to continuously improve the quality of human resources in order to compete in the global market. One effective way that must be done by human resource development to achieve this is to increase employee work motivation through a behavioral counseling approach with reward and punishment techniques. The purpose of this study is to comprehensively describe the role and function of human resource development in increasing work motivation through a behavioral counseling approach with reward and punishment techniques. The method used in this study is a field survey with structured interview techniques, participant observation, literacy studies, and documentation studies. The informants in this study numbered three people with a sampling technique using purposive sampling. The data processing method used is descriptive qualitative with triangulation techniques. Based on the results of the study and discussion, the author can conclude that the role and function of human resource development are very important in increasing employee work motivation. The application of a behavioral counseling approach with reward and punishment techniques that are consistent, fair, and transparent has empirically proven to be effective in changing behavior to be more adaptive so that it has a positive impact on improving employee performance.